Prospective Risk of Stillbirth and Neonatal Complications in Twin Pregnancies: Systematic Review and Meta-analysis. Issue 2 (June 2017) - Cheong-See, F.; Schuit, E.; Arroyo-Manzano, D.; Khalil, A.; Barrett, J.; Joseph, K.S.; Asztalos, E.; Hack, K.; Lewi, L.; Lim, A.; Liem, S.; Norman, J.E.; et al.
Abstract : ( BMJ . 2016;354:i4353) Twin pregnancies pose a high risk for stillbirth. Monochorionic twins have been reported to have a 13-fold increase and dichorionic twins a 5-fold increase compared to singleton pregnancies. As a result, it is sometimes decided to deliver uncomplicated twin pregnancies earlier to prevent late stillbirth. However, there is also risk of neonatal complications linked to preterm and early term delivery. The optimal gestational age for delivery of uncomplicated twin pregnancies is unknown. The present study aimed to determine the risks of stillbirth in women with uncomplicated monochorionic and dichorionic twin pregnancies, as well as the risks to the newborn when delivered at various gestational ages.